Becker congenital myotonia in black African with molecular findings - AZONBAKIN, Simon; ADOVOEKPE, Diane; ADJAGBA, Marius; ALAO MAROUFOU, MODJÉRÉ OLA MAROUFOU JULES; SAGBO, GODONOU GRATIEN; ADJIEN, KODJO CONSTANT; LALEYE, OLABISSI ANATOLE A. (My University, 2022)
Abstract Background: Congenital myotonia is a congenital disorder that affects skeletal muscles with myotonia. Affected muscles show stiffness and pain sometimes. The two major types of myotonia congenita are known as Thomsen disease and Becker disease. These conditions are distinguished by the severity of their symptoms and their patterns of inheritance. The causative factor is mutations in CLCN1 gene. Myotonia congenita is rarely reported in black especially in black African. Case presentation: This is a case report of Becker Congenital Myotonia in a 36-year-old male from Benin. The symptoms arose at the age of 7 years with regular and progressive course and muscles pains. Electromyogram, blood sampling, laboratory investigations and muscles biopsy confirm the diagnostic with molecular finding. Conclusion: The authors report a case of Becker congenital myotonia in a black African with molecular confirmation. Mexiletine was used as symptomatic agent with good results.
Keywords: Myotonia; Congenital; Becker disease; CLCN1 gene; Mexiletine